Selection and Validation of Housekeeping Genes as Reference for Gene Expression Studies in Pigeonpea (Cajanus cajan) under Heat and Salt Stress Conditions - Sinha, Pallavi; Saxena, Rachit K.; Singh, Vikas K.; Krishnamurthy, L.; Varshney, Rajeev K. (Frontiers in Plant Science, 2015)
To identify the stable housekeeping genes as a reference for expression analysis under heat and salt stress conditions in pigeonpea, the relative expression variation for 10 commonly used housekeeping genes (EF1α, UBQ10, GAPDH, 18SrRNA, 25SrRNA, TUB6, ACT1, IF4α, UBC and HSP90) was studied in root, stem and leaves tissues of Asha (ICPL 87119), a leading pigeonpea variety. Three statistical algorithms geNorm, NormFinder and BestKeeper were used to define the stability of candidate genes. Under heat stress condition, UBC, HSP90 and GAPDH were found to be the most stable reference genes. In the case of salinity stress, GAPDH followed by UBC and ACT1 were identified as the most stable reference genes. Subsequently, validation of the above identified genes was undertaken in qRT-PCR based gene expression analysis of two universal stress-responsive genes namely uspA and uspB genes. The relative quantification of these two genes varied according to the internal controls (most stable, least stable and combination of most stable and least stable housekeeping genes) and thus confirmed the choice as well as validation of internal controls in such experiments. The identified and validated housekeeping genes will facilitate gene expression studies under heat and salt stress conditions in pigeonpea.